Custodial Grandmothers' Psychological Distress, Dysfunctional Parenting, and Grandchildren's Adjustment - Smith, Gregory C. (2008)
An adaptation of the Family Stress Model (FSM) with hypothesized linkages between family contextual factors, custodial grandmothers' psychological distress, parenting practices, and grandchildren's adjustment was tested with structural equation modeling. Interview data from 733 custodial grandmothers of grandchildren between ages 4-17 revealed that the effect of grandmothers' distress on grandchildren's adjustment was mediated by dysfunctional parenting, especially regarding externalizing problems. The effects of contextual factors on grandchildren's adjustment were also indirect. The model's measurement and structural components were largely invariant across grandmothers' race and age, as well as grandchildren's gender and age. Group differences were more prevalent regarding the magnitude of latent means for model constructs. We conclude that parenting models like the FSM are useful for investigating custodial grandfamilies.